2021
DOI: 10.1111/cdoe.12689
|View full text |Cite
|
Sign up to set email alerts
|

Adult oral health‐related quality of life instruments: A systematic review

Abstract: To identify the existing OHRQoL instruments for adults, describe their scope (generic or specific), theoretical background, validation type, and cross-cultural adaptation. Methods: A systematic search was conducted and articles presenting validation of OHRQoL instruments in adults were included. Data were collected about the validation type: external validation (correlations/associations); or internal validation (Factor Analysis/Principal Components Analysis, Item Response Theory); and cross-cultural adaptatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 39 publications
0
35
0
4
Order By: Relevance
“…The heterogeneity across studies, regarding country, age, gender distribution, and time since stroke, limits the comparability of included studies. Similarly, the different assessment measurements of OHRQoL need to be recognized; although both OHIP and GOHAI are validated and appropriate for measuring OHRQoL, several differences exist between those measurements [ 44 ]. Furthermore, sub-scales of OHRQoL were rarely reported across included studies (see Table 5 ), making conclusions on the main reason for OHRQoL impairment (whether it is more functional or more psychosocial) speculative.…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneity across studies, regarding country, age, gender distribution, and time since stroke, limits the comparability of included studies. Similarly, the different assessment measurements of OHRQoL need to be recognized; although both OHIP and GOHAI are validated and appropriate for measuring OHRQoL, several differences exist between those measurements [ 44 ]. Furthermore, sub-scales of OHRQoL were rarely reported across included studies (see Table 5 ), making conclusions on the main reason for OHRQoL impairment (whether it is more functional or more psychosocial) speculative.…”
Section: Discussionmentioning
confidence: 99%
“…A higher total score indicated higher OHRQoL. This is the most common OHRQoL tool that is cross‐cultured and adhibited into diverse regions and age groups, 19 with good psychometric outcomes. The mandarin version of OHIP‐14 was proven to be reliable and valid in China 20…”
Section: Methodsmentioning
confidence: 99%
“…According to Google Scholar, the original development article of the 49-item OHIP [ 10 ] and its shorter version, OHIP-14 [ 11 ], have been cited 2,873 and 2,590 times as of December 10, 2021, both with an average of approximately 100 citations per year. A newly published systematic review of adult OHQoL instruments found that the OHIP-14 was the most frequently used (26.8%), while the OHIP-49 ranked third [ 12 ]. In addition, the literature suggests that the “OHIP-14 appeared to be responsive to change” [ 13 ].…”
Section: Introductionmentioning
confidence: 99%